Exploring parents' perceptions of computational thinking and its role in children's television - Breniel Lemley; Fashina Aladé (Future in Educational Research)
Abstract The rise in children's media use and the prioritization of STEM learning has led to the development of new STEM‐related apps, TV shows, and other media for young children, with several recent examples focused on computational thinking (CT). Learning CT at a young age can be beneficial to children's analytical and problem solving skills. Positive effects of educational media are best realized when the learning is scaffolded by a caregiver, but the ability of parents to scaffold CT lessons is understudied. This study explores parents' perceptions, understanding, and recognition of the CT cues embedded in a new television show for preschoolers. Qualitative semi‐structured interviews were conducted with 30 parents who, together with their children (ages 4–6), viewed two episodes of a new series. Interviews were transcribed and coded using thematic analysis. Most participants had never heard of CT before. When asked to define it, many parents highlighted aspects of CT in their definitions; however, their examples illustrated limited understanding of how CT might be taught to young children. Although some parents had reservations regarding the abstractness and age‐appropriateness of the topic, parents believed CT was an important topic for their children to learn. Research has shown that scaffolding can be beneficial to promoting CT learning in young children. Therefore, for creators of CT‐focused content, it is important that the curricular focus and learning goals are made very clear so that parents and caregivers can scaffold the material in a way that effectively supports their children's learning.